PROPAPHENON: CLINICAL PHARMACOLOGY AND EFFICACY IN SUPRAVENTRICULAR ARRHYTHMIAS (PART 2) - D. V. Preobrazhensky; A. V. Marenich; T. A. Andreychenko; V. G. Kiktev; B. A. Sidorenko (Российский кардиологический журнал)
Propaphenon: clinical pharmacology and efficacy in supraventricular arrhythmias (Part 2).